Cancer Phototherapy: Mitochondria‐Targeted Small‐Molecule Fluorophores for Dual Modal Cancer Phototherapy (Adv. Funct. Mater. 17/2016). (May 2016) - Luo, Shenglin; Tan, Xu; Fang, Shengtao; Wang, Yu; Liu, Tao; Wang, Xin; Yuan, Yi; Sun, Huiqin; Qi, Qingrong; Shi, Chunmeng
Abstract : Mitochondria play a central role in energy production and cell survival. On page 2826, Q. Qi, C. Shi, and co‐workers develop a multifunctional, mitochondria‐targeting, near‐infrared small‐molecule dye for synchronous cancer photodynamic and photothermal therapy. Its structure‐inherent cancer targeting and imaging capabilities also enable tumors and their margins to be visualized, providing potential for imaging‐guided cancer treatment.